(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article, our work outlines the principles of social equality in educational activities aimed at improving the legal mind and legal culture: publicity, openness and transparency, voluntary enforcement of obligations, the full expression of rules such as integrity and independence, organized in educational institutions failure to comply with these principles in activities aimed at improving legal minds and legal culture, legal activities of the educational institution by law enforcement agencies, (Matthew 24:14; 28:19 , 20) Jehovah’s Witnesses would be pleased to answers with you.